Knowledge, Attitude, And Practices Of Non-communicable Diseases: Comparison Between Orang Asli And Malay From Rural Area In Negeri Sembilan, Malaysia: A Comparative Study - Muslimah Ithnin; Norsham Juliana; Nadia Mohd Effendy; Mohd Dzulkhairi Mohd Rani; Nadeeya'ayn Umaisara Mohamad Nor (Malaysian Journal of Public Health Medicine (MJPHM), 2024)
Volume: 20 No: 2 (page: 131-140)